SOCIO-PROFILE CHARACTERISTICS OF POSTGRADUATES OF SRI VENKATESWARA VETERINARY UNIVERSITY, TIRUPATI AND CONSTRAINTS ENCOUNTERED TO GAIN EMPLOYABILITY - M.V. Prasanna; G. Triveni; B. Subrahmanyeswari; P. Asha lathe (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The veterinary graduates and postgraduates should be enabled with professional abilities and employability skills to be successful in the competitive technology driven world. In order to know the background and socio-profile characteristics of the respondents, it is important to analyse these characteristics in depth. The socio-profile characteristics of people vary with the location to location, time to time and society to society. Therefore, the study was undertaken to study the socio-profile characteristics of postgraduates of SVVU and constraints faced by them to gain employability. The results of the research revealed that majority (53.34 %) of the post graduates belonged to first class category of academic performance and majority (66.7 %) of post graduates belonged to 24-27 years of age group. Nearly half (56.70 %) of them belonged to open category and half of the postgraduates hailed from the rural background. Majority (77.50%) of respondents were with medium annual family income and half (50 %) of their fathers were farmers. Majority (80.00 %) of the postgraduates had medium level of exposure to college library. While 61 per cent of them were aware of the job Veterinary Assistant Surgeon (VAS) and preferred VAS job after completion of B. V. Sc & AH. Majority (65.00 %) of the respondents had medium achievement motivation and 61.7 per cent of them were with medium level of hard work. The foremost constraints faced by the postgraduates were poor involvement of the students in learning process and lack of interest among the scholars to develop the employability skills.